2011
DOI: 10.1038/laban0311-85
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of tramadol, carprofen or multimodal analgesia in rats undergoing ventral laparotomy

Abstract: In this study, the authors evaluated the analgesic efficacy of tramadol (an opioid-like analgesic), carprofen (a nonsteroidal anti-inflammatory drug) and a combination of both drugs (multimodal therapy) in a rat laparotomy model. The authors randomly assigned rats to undergo either surgery (abdominal laparotomy with visceral manipulation and anesthesia) or anesthesia only. Rats in each group were treated with tramadol (12.5 mg per kg body weight), carprofen (5 mg per kg body weight), a combination of tramadol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…Thus, the side effect profile of all drugs has to be analyzed carefully. For rodents, several effective multimodal analgesia protocols have been described, with examples including tramadol-carprofen 69 or fentanyltrazodone-paracetamol 70 .…”
Section: Multimodal Therapies and Local Anesthesiamentioning
confidence: 99%
“…Thus, the side effect profile of all drugs has to be analyzed carefully. For rodents, several effective multimodal analgesia protocols have been described, with examples including tramadol-carprofen 69 or fentanyltrazodone-paracetamol 70 .…”
Section: Multimodal Therapies and Local Anesthesiamentioning
confidence: 99%
“…Cannon et al . 3 reported skin lesions in rats given tramadol which was later determined to be due to hyperosmolarity of the product (unpublished data). Buprenorphine has also been reported to have respiratory depression when given at 10 mg/kg doses 62 .…”
Section: Discussionmentioning
confidence: 96%
“…We incorporated several parameters: feed consumption, body weight, clinical signs, open field activity, and running wheel to evaluate physiologic and behavior changes as previously done by this laboratory 1,3 . Buprenorphine has been shown to decrease feed intake and reduce body weight or weight gain in rodents 4,32,54–60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…83 Results of several studies in rats have shown that tramadol can be an effective analgesic for acute pain. [85][86][87][88] In rats, tramadol provided analgesia for osteoarthritis, 85 but its efficacy decreased with increased duration of pain, and its antinociceptive mechanism changed over time, which may partially explain its inconsistent efficacy in patients with chronic pain. 86 Anecdotally, oral tramadol doses of 2 to 10 mg/kg have been well tolerated in rabbits and rats.…”
Section: Meloxicammentioning
confidence: 99%